Incidental detection of retained oil‐based hysterosalpingography contrast medium on postoperative postpartum radiography: A case report - Harue Hayashida; Kiichiro Furuya; Hiroki Kurahashi; Saya Yamashita; Yangsil Chang; Hiroaki Tsubouchi; Kayoko Shikado; Kazuhide Ogita (Clinical Case Reports, 2022)
Abstract Hysterosalpingography is widely performed in assisted reproductive technology. We present a rare case of contrast medium retention which was incidentally found and mimicked a retained surgical instrument. A medical history of treatment for infertility can facilitate the differential diagnosis of abnormal findings on post‐caesarean section radiography.